Juvenile burrowing owl movement and survival in a human‐altered landscape - Eboni Griffin; Martha Desmond; Dawn VanLeeuwen (Wildlife Society Bulletin)
ABSTRACT Burrowing owls (Athene cunicularia) are increasingly moving into human‐altered landscapes, yet it is not well‐understood how these environments affect movements and survival. We studied postfledging juvenile burrowing owls (n = 42) in urban, greenspace, and agricultural environments in New Mexico, USA, during 2012 and 2013. Agriculture was divided into heterogeneous and homogenous blocks (up to 1,000‐m radius from nest) based on land‐cover continuity. Postfledging movement distance (n = 31) was not influenced by year, sex, or landscape metrics within 600 m of the nest. Landscape metrics, however, did not account for visual barriers to movement including pecan orchards and residential areas within the agricultural landscape. Movement distances did vary by dominant environment, with owls in urban landscapes (80.9 m ± 20.1 SE, n = 4) moving shorter distances than owls in greenspace (552.7 m ± 117.0 SE, n = 7), homogenous agriculture (497.8 m ± 140.6 SE, n = 7), and heterogeneous agriculture (206.7 m ± 36.3 SE, n = 13). Juvenile postfledging survival was greater in landscapes with a greater percentage of agriculture (β = 0.017, 95% CL = 0.017–0.018). Survival was greatest in heterogeneous and homogeneous agriculture (93% and 89%, respectively) followed by urban (67%) and greenspace (50%) environments. Greenspace had the greatest mortality rate, but was negatively correlated with agriculture, making it difficult to ascertain whether one of these metrics had a stronger influence on survival. Increased mortality in greenspace suggests urban parks and patches of native vegetation adjacent to urban development do not protect young owls. Owls in larger expanses of continuous cover had greater movements and utilized more satellite burrows. Programs managing for burrowing owls in human‐altered landscapes should avoid establishing artificial burrows and translocation sites in greenspace adjacent to urban areas, and, in the southwestern United States, should focus on agricultural areas. © 2017 The Wildlife Society.